Implementasi Pendekatan Saintifik dengan Metode Role Playing pada Pembelajaran Kurikulum 2013 untuk Mempermudah Penilaian Individu - Budi Sasomo (LPPM Press, 2015)
This research had attempted to find out a solution for teacher in assessing individuallearners authentically. The method used in the preparation of this article is derived fromthe literature review to obtain formulation of the problem, data collection, discussion,conclusion and suggestion. Based on the hypothesis testing using t test, it was concludedthat Role Play method combined with a Scientific approach obtained better learningachievement than those taught using Lecture method or Direct Learning. It provided anew alternative for the implementation of the learning curriculum in 2013 using the RolePlay combined with the Scientific Approach. In the process of learning, the teachers orlecturers were both greatly helped by the application of this method. That was becausethe learners were required to demonstrate their abilities individually in front of the classwhen learning activities took place.